2010
DOI: 10.1155/2011/951258
|View full text |Cite
|
Sign up to set email alerts
|

Different Brain Network Activations Induced by Modulation and Nonmodulation Laser Acupuncture

Abstract: The aim of this study is to compare the distinct cerebral activation with continued wave (CW) and 10 Hz-modulated wave (MW) stimulation during low-level laser acupuncture. Functional magnetic resonance imaging (fMRI) studies were performed to investigate the possible mechanism during laser acupuncture stimulation at the left foot's yongquan (K1) acupoint. There are 12 healthy right-handed volunteers for each type of laser stimulation (10-Hz-Modulated wave: 8 males and 4 females; continued wave: 9 males and 3 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…The distinct cerebral activation was observed during low-level laser acupuncture (continued wave and 10 Hz-modulated wave stimulation) at KI1 of the left foot in healthy right-handed volunteers [14]. Most of the activated areas, observed by functional magnetic resonance imaging, were involved in the functions of memory, attention, and self-consciousness.…”
Section: Vascular Dementia (Vd)mentioning
confidence: 90%
“…The distinct cerebral activation was observed during low-level laser acupuncture (continued wave and 10 Hz-modulated wave stimulation) at KI1 of the left foot in healthy right-handed volunteers [14]. Most of the activated areas, observed by functional magnetic resonance imaging, were involved in the functions of memory, attention, and self-consciousness.…”
Section: Vascular Dementia (Vd)mentioning
confidence: 90%
“…25 It has been reported that SI processing is performed with input provided by mechanoreceptors, 26 but the activation of much of the SI has not been conˆrmed by acupuncture stimulation. 1,2,[4][5][6][7][8][10][11][12][13][14] The peripheral receptors involved in acupuncture stimulation have been suggested to be the polymodal receptors that are nociceptive receptors of the C-ˆbers. 27 It is also thought that the input is the transmission through C-ˆber in response to production of a chemical substance following deep tissue injury by manual acupuncture stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 20 years, the development of imaging techniques, such as functional magnetic resonance imaging (fMRI), has opened the door for the study of brain activity in response to acupuncture stimulation. Numerous studies have been performed with fMRI and a variety of acupuncturerelated stimulations, such as electroacupuncture, 1,2 manual acupuncture, [1][2][3][4][5][6][7][8][9][10][11][12][13] sham acupuncture of the skin some distance from a known acupoint [4][5][6] or by noninsertive acupuncture and poking of the skin over an acupuncture point, [7][8][9][10][11] pressure to the acupoint, 12 laser acupuncture, 13 and electrical acupoint stimulation. 14 fMRI studies of acupuncture have typically utilized a block design that is used as a general linear model regressor in the analysis of fMRI data based on the assumption that mechanoreceptors and nociceptor-associated aŠerence work coincidentally with acupuncture stimulation, which is the conscious perception and evaluation of this aŠerence.…”
Section: Introductionmentioning
confidence: 99%
“…The posterior middle cingulate cortex, receiving information from insula, appeared to be important in coding acupuncture sensation intensity, then interacting with the posterolateral parietal cortex in orienting the body in response to somatosensory stimuli (Vogt, 2005). Recently, a functional imaging study also suggested a central role for the precuneus in a wide spectrum of highly integrated tasks (Hsieh et al, 2010). Based on these reports and present findings, we speculate that these structures may be responsible for integration of the sensory inputs associated with pain and proprioceptors, and the motor cortices for manifestation of cross education.…”
Section: Discussionmentioning
confidence: 99%